Top Management Team Advice Seeking and Exploratory Innovation: The Moderating Role of TMT Heterogeneity - Alexiev, Alexander S.; Jansen, Justin J. P.; Van den Bosch, Frans A. J.; Volberda, Henk W. (Journal of Management Studies, 2010)
abstractResearch on strategic decision making has considered advice‐seeking behaviour as an important top management team attribute that influences organizational outcomes. Yet, our understanding about how top management teams utilize advice to modify current strategies and pursue exploratory innovation is still unclear. To uncover the importance of advice seeking, we delineate between external and internal advice seeking and investigate their impact on exploratory innovation. We also argue that top management team heterogeneity moderates the impact of advice seeking on exploratory innovation. Findings indicated that both external and internal advice seeking are important determinants of a firm's exploratory innovation. In addition, we observed that top management team heterogeneity facilitates firms to act upon internal advice by combining different perspectives and developing new products and services. Interestingly, heterogeneous top management teams appeared to be less effective to leverage external advice and pursue exploratory innovation.